ASSESSMENT OF THE CONSEQUENCES OF ELECTION POLITICAL VIOLENCE ON DEMOCRATIC SOCIAL ORDER IN NIGERIA - Mezieobi, S.A.; Mezieobi, D.I.; Anyanwu, Jerome (Advances in Social Sciences Research Journal, 2017)
This study assessed the consequences of political election violence on democratic social order in Nigeria. The study was carried out in North central geo-political zone of Nigeria. The population of the study was 200 respondents across the area of study. Data was generated through structured interviews. Three research questions guided the study. The study was focused on causes of political violence in Nigeria, the consequences and how to improve the scenario for institutionalization of credible democratic order in Nigeria. It was found that ethnicity and religion, doctoring of election results, massive rigging, poverty, thuggery amongst others stimulated political election violence. Some of the consequences were: non mass oriented governance, political instability, increased cost in maintenance of security, political assassination and so on the study found that national integration, fair distribution of resources by leadership, indigenous language utilization, political education amongst others can sanitize the democratic process. It was recommended that leadership should be focused on pursuit of national interest aspiration ventures, fair treatment of all citizens of Nigeria, irrespective of tribe and the institutionalization of laws against fraudulent elections. Keywords: Assessment, election political violence and democratic social order.